Optimal DNA Isolation Method for Detection of Nontuberculous Mycobacteria by Polymerase Chain Reaction - Mohammadi, Samira (Adv Biomed Res, 2017)
BACKGROUND: Nontuberculous mycobacteria (NTM) are a group of opportunistic pathogens and these are widely dispersed in water and soil resources. Identification of mycobacteria isolates by conventional methods including biochemical tests, growth rates, colony pigmentation, and presence of acid-fast bacilli is widely used, but these methods are time-consuming, labor-intensive, and may sometimes remain inconclusive. MATERIALS AND METHODS: The DNA was extracted from NTM cultures using CTAB, Chelex, Chelex + Nonidet P-40, FTA(®) Elute card, and boiling The quantity and quality of the DNA extracted via these methods were determined using UV-photometer at 260 and 280 nm, and polymerase chain reaction (PCR) amplification of the heat-shock protein 65 gene with serially diluted DNA samples. RESULTS: The CTAB method showed more positive results at 1:10–1:100,000 at which the DNA amount was substantial. With the Chelex method of DNA extraction, PCR amplification was detected at 1:10 and 1:1000 dilutions. CONCLUSIONS: According to the electrophoresis results, the CTAB and Chelex DNA extraction methods were more successful in comparison with the others as regard producing suitable concentrations of DNA with the minimum use of PCR inhibitor.